Project management in laboratory medicine - Lippi Giuseppe; Mattiuzzi Camilla (Journal of Medical Biochemistry, 2019)
The role and responsibilities of laboratory managers have considerably evolved during the past decades. This revolution has been mostly driven by biological, technical, economic and social factors, such as deepened understanding of the pathophysiology of human diseases, technical innovations, renewed focus on patient safety, cost-containment strategies and patient empowerment. One of the leading consequences is an ongoing process of reorganization, consolidation and automation of laboratory services, whose propitious realization strongly relies on establishing an efficient project management plan. In a practical perspective, the leading drivers of project management in laboratory medicine encompass various activities supporting a clear definition of the local environment, an accurate planning of technical resources, the acknowledgement of staff availability and qualification, along with the establishment of a positive and constructive interplay with hospital administrators. Therefore, the aim of this article is to provide a personal overview on the main drivers and outcomes of project management in laboratory medicine, which will expectedly contribute to construct a new consciousness and an innovative and multifaceted job description of laboratory professionals worldwide.